The threshold of anxiety in low-stakes testing for foreign language reading - Mikami, Hitoshi; Chi Yui Leung; Yoshikawa, Lisa (Reading in a foreign language, 2018)
The following question has yet to be answered by researchers: when does anxiety have a systematic downward bias on foreign language (FL) reading test scores? The results of the correlation and regression analyses conducted in this study indicate that, at least in the case of university-level English learners in Japan, anxiety-induced bias occurs in a low-stakes FL reading test when the test becomes objectively challenging for students. Our data also suggest that concerns about unsuccessful text comprehension play a central role in the elevation of anxiety in a low-stakes test situation.